Restrukturisasi kognitif untuk menurunkan kecemasan masa depan pada dewasa awal - Tazkiya Hanif Rahma; Diana Savitri Hidayati (Universitas Muhammadiyah Malang, 2026)
Future anxiety is a condition that arises from recurring negative thoughts about the uncertainty of the future. This study aims to examine the effectiveness of cognitive restructuring in reducing future anxiety in young adults. The subject was an 18-year-old female who experienced anxiety related to concerns about career failure and interpersonal relationships. Assessment methods included interviews, observation, CFIT, graphic tests (DAP, BAUM, HTP), SSCT, and the Dark Future Scale. The intervention was conducted using cognitive restructuring techniques to identify and modify irrational thoughts. The results showed a decrease in anxiety scores from 32 (high category) to 20 (moderate category), indicating a reduction of 12 points. Qualitatively, the subject demonstrated improved ability to challenge negative thoughts and make more realistic and adaptive decisions. These findings indicate that cognitive restructuring is effective in reducing future anxiety and has implications for improving individual psychological functioning.